Molecular imaging in the investigation of hypoglycaemic syndromes and their management. Issue 6 (June 2017) - Pattison, David A; Hicks, Rodney J
Abstract : There has been recent progress in molecular imaging using a variety of cellular targets for the investigation of adult non-diabetic hypoglycaemic syndromes and its integration into patient management. These targets include peptide receptors (somatostatin receptors (SSTRs) and glucagon-like peptide-1 receptor (GLP-1R)) the amine precursor uptake and decarboxylation system utilising the diphydroxyphenylaline (DOPA) analogue 6-[ 18 F]-l -fluoro-l -3, 4-dihydroxyphenylalanine ( 18 F-FDOPA), and glycolytic metabolism with 2-[ 18 F]fluoro-2-deoxy-d -glucose (FDG). Accurate preoperative localisation and staging is critical to enable directed surgical excision or enucleation with minimal morbidity and preservation of residual pancreatic function. Benign insulinoma has near ubiquitous dense GLP-1R expression enabling accurate localisation with radiolabelled-exendin-4 compounds (e.g. 68 Ga-NOTA-exendin-4 PET/CT), whilst the rarer and more difficult to manage metastatic insulinoma typically express SSTR and is preferably imaged with radiolabelled-SSTR analogues such as 68 Ga-DOTA-octreotate (DOTATATE) PET/CT for staging and assessment of suitability for peptide receptor radionuclide therapy (PRRT). Similar to other metastatic neuroendocrine tumours, FDG PET/CT is used in the setting of higher-grade metastatic insulinoma to provide important prognostic information that can guide treatment and determine suitability for PRRT. Interestingly, these three tracers appear to represent a spectrum of differentiation, which we conceptually describe as the 'triple-flop' phenomenon, with GLP-1R > SSTR > FDG in benign insulinoma and the opposite in higher-grade disease. This paper will review the clinical syndromes of adult hypoglycaemia (including a practical overview of the differential diagnoses to be considered), comparison of techniques for insulinoma localisation with emphasis on molecular imaging before discussing its implications for management of metastatic insulinoma.